2020
DOI: 10.21203/rs.2.21735/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-operative denosumab is associated with higher risk of local recurrence in giant cell tumor of bone: a systematic review and meta-analysis

Abstract: Background: In 2013, denosumab was introduced as peri-operative adjuvant treatment for giant cell tumor (GCT) of bone as it inhibits osteoclast activity. It is suggested that denosumab relives pain, facilitate curettage in lesions requiring resection initially. However, controversy remains whether denosumab increases the risk of local recurrence after surgery.Methods: Medline, Embase and the Cochrane Library were comprehensively searched in June 2019 to identify studies investigating the clinical outcome of GC… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Denosumab has helped in facilitating curettage in lesions with extensive bone loss and/or a cortical break with a large soft tissue component. The benefit of using preoperative denosumab to facilitate curettage is tempered by concern regarding the increased rate of local recurrence after denosumab treatment (Chen et al, 2020;Perrin et al, 2021). The study of Mak et al (2014) showed that cell proliferation is only diminished by denosumab; the cells continue to proliferate in vitro, though at a slower rate.…”
Section: Discussionmentioning
confidence: 99%
“…Denosumab has helped in facilitating curettage in lesions with extensive bone loss and/or a cortical break with a large soft tissue component. The benefit of using preoperative denosumab to facilitate curettage is tempered by concern regarding the increased rate of local recurrence after denosumab treatment (Chen et al, 2020;Perrin et al, 2021). The study of Mak et al (2014) showed that cell proliferation is only diminished by denosumab; the cells continue to proliferate in vitro, though at a slower rate.…”
Section: Discussionmentioning
confidence: 99%
“…Many of last year's published papers on GCTB treatment express concerns on an increased recurrence risk after denosumab but must be interpreted with the following concerns in mind. Three systematic reviews and meta-analyses were published, with an overlap of seven of the included studies [35][36][37]. In the majority of these studies, no matching was performed for tumor size, extension, or Campanacci grade and conclusions are subject to indication bias.…”
Section: Local Recurrence After Denosumabmentioning
confidence: 99%
“…The authors believed denosumab may be associated with an increase in local recurrence although the evidence was weak due to lack of randomized studies and indication bias. In another meta-analysis covering 10 studies with 1,082 cases, Chen et al ( 46 ) found that denosumab therapy was correlated with higher local recurrence rate and inferior 5-year recurrence-free survival.…”
Section: Denosumab May Increase the Risk Of Local Recurrence In Patiementioning
confidence: 99%